Examining the Domestic Sex Labour Industry in Nepal: Perspectives from Hotels, Streets, and Restaurants - Ghimire, Mayanath; Magar, Prem Kumari; Mishra, Anjay Kumar (Intellectual Journal of Academic Research, 2025)
The investigator examined research results related to the topic that have appeared in publications at both national and international scales. Female enumerators were employed to engage with female sex workers and assured them of the confidentiality of their personal details and locations. The collected data were analysed, and a report was generated. The reasons for engaging in sex work can include the inability to meet personal needs, expenses related to raising and educating children, daily household costs, and money for festival celebrations. Women without a steady income, facing unemployment, experiencing loneliness, suffering from psychological stress, dealing with domestic violence, or having a husband who remarries, may resort to sex work as a means to cover debts or seek a new source of income. Three categories of female sex workers have been identified in the mid-eastern region of Nepal. These include those operating on the streets, those working from home, and those affiliated with established locations. Their earnings range from NRs. 500 to 20,000 depending on various factors. Travel expenses are higher compared to other costs. Sex workers frequently encounter issues such as low pay, sexual violence, theft, and physical aggression from clients. Among these groups, street-based sex workers remain the most at risk compared to their home-based and established counterparts. Consider non-criminal labour performed legally, shifting the viewpoint to acknowledge it with equal respect as other professions associated with female sex workers. Offer health insurance, avoiding police arrests, and treat sex work as a legitimate occupation. Recognize and value sex workers as professionals in their field.